Pandangan Penghulu Terhadap Pemberian Mahar Berupa Hafalan Al-Qur’an Perspektif Hukum Islam (Studi Kasus KUA di Surabaya) - Al Farisi, Salman; Maqfiroh, Siti (Maqasid: Jurnal Studi Hukum Islam, 2022)
The new form of a dowry is a form of memorization of verses from the Qur'an. Regarding the dowry used during the marriage contract, it cannot be separated from a headman who serves as a facilitator of a marriage. This research is a field research where the researcher goes directly to the field. The methodology used in this research is a qualitative which produces data in the form of written description. The data are collected by conducting interviews and documentation. The results of the research show that the headmen of KUA (office of religious affairs) in the region of Surabaya have different opinions regarding to this aspect. Some say that it is allowed to use memorization of the Qur'an as a dowry, but there are also those who do not agree if the Qur'an memorization is used as a dowry. The headman agrees because this is based on the KHI that dowry can be in the form of services. This opinion is also in line with the opinion of the Syafi'i and Hambali schools of thought. Meanwhile some headmen disagree because their opinion is in line with the Maliki and Hanafi schools of thought. Keywords: The perspective of a headman, Marriage, Mahr of Memorization of the Qur'an, Islamic Law.